2019
DOI: 10.1111/tbj.13203
|View full text |Cite
|
Sign up to set email alerts
|

Internet use and preferences among women living with advanced breast cancer

Abstract: Despite high distress and unmet informational and psychosocial needs, and recommendations for development of advanced breast cancer (ABC)‐specific resources, there remains a paucity of appropriate, accessible psychological interventions. This survey study examined internet use and preferences of women with ABC, to gauge feasibility of providing an ABC‐specific internet intervention. Most participants (83%) used the internet daily. Results indicated most women with ABC would find an ABC‐specific internet interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…The open trial demonstrated the feasibility of the online intervention with no major barriers to recruitment and participants engaging well in the trial. This is in keeping with two recent studies of women with metastatic breast cancer showing firstly, high rates of internet use ( Kemp et al, 2019 ) and secondly, increasing comfort in accessing online support ( Kemp et al, 2018 ). The rates of progression of cancer were unexpected and may be accounted for by the heterogeneous mix of cancer types.…”
Section: Discussionsupporting
confidence: 90%
“…The open trial demonstrated the feasibility of the online intervention with no major barriers to recruitment and participants engaging well in the trial. This is in keeping with two recent studies of women with metastatic breast cancer showing firstly, high rates of internet use ( Kemp et al, 2019 ) and secondly, increasing comfort in accessing online support ( Kemp et al, 2018 ). The rates of progression of cancer were unexpected and may be accounted for by the heterogeneous mix of cancer types.…”
Section: Discussionsupporting
confidence: 90%
“…Previous investigations have already demonstrated the Internet as a tool to support women with breast cancer. Nowadays, considering the facilities to access this tool, strategies to offer information on adverse events related to the cancer treatment, as well as emotional support, may be relevant 14,15 .…”
Section: Discussionmentioning
confidence: 99%
“…Digital health tools, such as web-based therapy, could address these barriers. Given digital health tools provide 24/7 access at a time and place convenient to the patient, and reduce obligations to spend valued time and money in healthcare settings, this mode of providing psychosocial care has particular pertinence to women with MBC [ 20 ]. Furthermore, digital interventions are easily scalable, can be immediately updated as new evidence emerges, and provide the flexibility to explore content in a non-linear way, with patients able to access information pertinent to their most immediate needs [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, digital interventions are easily scalable, can be immediately updated as new evidence emerges, and provide the flexibility to explore content in a non-linear way, with patients able to access information pertinent to their most immediate needs [ 21 ]. While there are no published online intervention RCTs in this population, women with MBC are already seeking cancer-related information on the internet [ 20 ] and are receptive to the online provision of a psychosocial program [ 22 ]. The rapidly building evidence base in early-stage cancer populations for improving distress [ 23 , 24 ], depression and anxiety [ 25 ], fear of recurrence [ 26 ], QOL [ 27 , 28 ], and health service utilisation [ 27 ], can help to inform future MBC-specific intervention development.…”
Section: Introductionmentioning
confidence: 99%